The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1152/ajpendo.1993.265.1.e176
|View full text |Cite
|
Sign up to set email alerts
|

Clenbuterol mimics effects of innervation on myogenic regulatory factor expression

Abstract: The amelioration of denervation atrophy by the beta-adrenoceptor agonist clenbuterol has led to the suggestion that the drug mimics or stimulates production of neurotrophic factors. Neurotrophic factors have profound effects on muscle growth, but the precise mechanisms through which this influence is exerted are unknown. The expression of myoD and myogenin, proteins that in turn regulate the transcription of tissue-specific genes during skeletal muscle differentiation, is controlled by innervation. In muscle u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…It has been previously reported that SMN is phosphorylated at serines 28 and (8,12,14). ␤-Adrenergic agonists have been shown to improve muscle strength in human subjects with healthy and diseased muscle (29)(30)(31), and daily albuterol treatment had beneficial effects in an open-label pilot study in SMA type II and III patients (16). Salbutamol has been also been shown to increase SMN protein levels in patient-derived fibroblasts (1).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that SMN is phosphorylated at serines 28 and (8,12,14). ␤-Adrenergic agonists have been shown to improve muscle strength in human subjects with healthy and diseased muscle (29)(30)(31), and daily albuterol treatment had beneficial effects in an open-label pilot study in SMA type II and III patients (16). Salbutamol has been also been shown to increase SMN protein levels in patient-derived fibroblasts (1).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that clenbuterol represses the expression of MyoD and myogenin in denervated rat soleus muscles [34], and that clenbuterol administration increased myogenin expression in immobilized rat plantaris muscles [35]. Clenbuterol administration also increased MyoD expression in rat soleus muscles [36].…”
Section: Discussionmentioning
confidence: 95%
“…The increased percentage of hybrid fibres coexpressing two or more MHC isoforms provides support for the postulate that the slow-to-fast MHC shift results rather from the transition of preexisting fibres than from the formation of new fibres via activation of satellite cell differentiation (Maltin et al 1986). The effects of clenbuterol on MRF expression have not been clearly defined and increased (Hughes et al 1993, Mozdziak et al 1998 or no effects (Maltin et al 1993, Delday & Maltin 1997 have been reported on MyoD mRNA levels after clenbuterol administration. Our results show for the first time that the clenbuterolinduced slow-to-fast transition in MHC isoforms was associated with an increase in the MyoD protein content.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel with the calcineurin-nuclear factor of activated T cells (NFAT) and mitogen-activated protein kinase (MAPK) pathways, the myogenic regulatory factors (MRFs) are candidate regulators for the gene expression of proteins determining the myofibre phenotype. The changes in MyoD mRNA levels are controversial, increased MyoD mRNA has been reported after clenbuterol administration (Hughes et al 1993, Mozdziak et al 1998, while other studies failed to demonstrate any change in MyoD mRNA (Maltin et al 1993, Delday & Maltin 1997). MyoD, a member of the MRF family, accumulates in fast-twitch muscles, and previous studies reported an association between changes in muscle phenotype and the expression of this regulatory factor (Hughes et al 1993(Hughes et al , 1997.…”
mentioning
confidence: 99%